Knowledge, Attitude and Practice on Birth Preparedness and Complication Readiness among Pregnant Women Attending in an Antenatal Clinic - Subedi, Sabitra; Mukhia, Suzanna (Journal of Nursing Education of Nepal, 2023)
Introduction: Birth preparedness and complication readiness is the process planning for normal  birth and anticipating the action needed in case of an emergency. Promoting birth and emergency  planning helps to improve preventive behaviour, increase awareness of mothers about danger signs and  improvement in care seeking behaviour in the case of obstetric complication.  Methods: Cross- sectional descriptive study was conducted to find out knowledge, attitude and practice  on birth preparedness and complication readiness among pregnant women attending in antenatal clinic  of institution based family planning clinic at Koshi Zonal Hospital, Biratnagar. Data were collected  from 116 pregnant women of second ANC visit and above using structured interview schedule in four  weeks. Results: The findings of the study revealed that majority of respondents (69%) were between ages  21- 30 years with the mean age of 23.7±3.2 years. This study depicts that 28.4% of the respondents  had inadequate knowledge, 50% of the respondents had moderately adequate knowledge and 21% of  the respondents had adequate knowledge. All of the respondents had favorable attitude and 43.1%  had inadequate practice, 37.1% of respondents had moderate adequate practice and only 19.8%  of respondents had adequate practice. The results revealed that only (9.5%) of respondents were  well prepared. Analysis using kruskal Wallis identified statistically significant association between  knowledge and practice (p=0.006). Conclusion: This study identified inadequate knowledge and practices on birth preparedness and  complication readiness. Thus, antenatal care clinics should give due emphasis to preparation for birth  and its complication and provide information and education to all pregnant women.
Keywords: Attitude; Birth Preparedness; Complication Readiness; Knowledge; Practice